A lidocaine-containing cross-linked collagen implant and a method for preparing the same
Patent Information
- Application Number
- CN202610137166.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-01-30
AI Technical Summary
胶原蛋白植入剂主要解决传统填充材料生物相容性不足、维持效果短暂、易引发免疫排斥或炎症反应等问题,同时针对软组织缺损、皮肤老化导致的形态异常等临床需求,提供兼具支撑性与再生诱导性的解决方案
与现有技术相比,本发明含利多卡因的交联胶原蛋白植入剂并非单纯的物理填充,而是从物理填充与支撑、细胞支架引导与组织整合、降解与替代的多角度、多方向进行联动展开作用。具体如下:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of collagen technology, and more particularly to a lidocaine-containing cross-linked collagen implant and its preparation method. Background Technology
[0002] Collagen implants are injectable biomedical materials made with collagen as the core component. They possess excellent biocompatibility, biodegradability, and tissue adhesion. Their main applications include medical aesthetics, regenerative medicine, and soft tissue repair, specifically for facial wrinkle filling, repair of depressed tissue, skin tightening and anti-aging, and scar repair. Collagen implants primarily address the shortcomings of traditional filler materials, such as insufficient biocompatibility, short-lived effects, and susceptibility to immune rejection or inflammatory reactions. They also provide solutions that combine support and regenerative induction for clinical needs such as soft tissue defects and morphological abnormalities caused by skin aging.
[0003] To further optimize the effects, various functional substances can be compounded, such as growth factors that synergistically promote tissue regeneration, stem cell extracts, hyaluronic acid, hydroxyapatite microspheres, vitamin C, glutathione, ceramides, etc., as well as polysaccharides such as amino acids, chitosan, and sodium hyaluronate that improve material stability and bioactivity. This compounding achieves a synergistic effect of multiple functions, including filling and support, regeneration and repair, and anti-oxidation and anti-aging. Improving the storage stability of collagen implants can be achieved by optimizing storage conditions and formulation, such as using low-temperature refrigeration or freezing to avoid high temperatures, strong light, and repeated freeze-thaw cycles, while adding mild stabilizers such as amino acids and chitosan to inhibit collagen molecule aggregation and degradation; or using aseptic vacuum sealing or nitrogen-filled packaging to isolate oxygen, and combining it with antioxidants such as vitamin C derivatives to further reduce the risk of oxidation and microbial contamination, extending the product's shelf life.
[0004] CN117085178A discloses an injectable facial filler composition for cosmetic surgery and its preparation method. The facial filler composition consists of hyaluronic acid, polylactic acid gel, collagen, anesthetic, and an aqueous solution for injection. The preparation method of this invention first dissolves hyaluronic acid-polylactic acid in an aqueous solution for injection, allows it to stand and swell, then adds an anesthetic, and finally sterilizes it by stirring and adds collagen to obtain the final product.
[0005] CN113797389A discloses a human skin cosmetic wrinkle-removing filler and its preparation method. The filler is composed of non-animal-derived hyaluronic acid, human-like collagen, fish collagen peptide antioxidant enzyme, dextran, hydroxyapatite calcium, and botulinum toxin. This invention's human skin cosmetic wrinkle-removing filler has the characteristics of good cosmetic wrinkle-removing effect, high safety, and long-lasting effect, and is applied by injection into the dermis layer of the face where filling is needed.
[0006] The solutions reported in these patent documents do not simultaneously solve the problems of stability and postoperative skin hydration in cosmetic injections of cross-linked collagen implants. Summary of the Invention
[0007] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to improve the thermal stability of cross-linked collagen implants and the postoperative skin water retention.
[0008] To achieve the above objectives, the present invention provides a lidocaine-containing cross-linked collagen implant and a method for preparing the same.
[0009] The preparation method of the lidocaine-containing cross-linked collagen implant includes the following specific steps, in parts by weight: (1) Collagen dissolution and cross-linking: Disperse 3-4 parts of type I collagen in 80-90 parts of PBS buffer, stir at 400-600 rpm for 0.5-1.5 hours to form a homogeneous collagen solution, add 10-20 parts of glutaraldehyde aqueous solution and stir at 2-8℃ for 22-26 hours to obtain cross-linked collagen, add 900-1100 parts of water to centrifuge and wash the cross-linked collagen, add 900-1100 parts of 3-4wt% lysine aqueous solution, and finally add 900-1100 parts of water to centrifuge and wash the cross-linked collagen to obtain cross-linked collagen wet material; (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is vacuum freeze-dried to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 10-20 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production process environment, 1-3 parts of sterile cross-linked collagen freeze-dried cake are redispersed in 360-380 parts of sterile PBS buffer and homogenized to make it into a uniform viscous suspension; 10-20 parts of sterile lidocaine hydrochloride solution are added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately to obtain the lidocaine-containing cross-linked collagen implant; Alternatively, under aseptic production conditions, 1-3 parts of sterile cross-linked collagen freeze-dried cake are redispersed in 360-380 parts of sterile PBS buffer and homogenized to form a uniform viscous suspension; 0.6-1 parts of functional monosaccharide and 10-20 parts of sterile lidocaine hydrochloride solution are added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately to obtain the lidocaine-containing cross-linked collagen implant.
[0010] In step (1), the glutaraldehyde aqueous solution is a 3-5 wt% glutaraldehyde aqueous solution.
[0011] In step (3), the functional monosaccharide is one of α-galactose, glucose, or β-mannose.
[0012] The sterile lidocaine hydrochloride solution in step (3) is a 5-10 wt% sterile lidocaine hydrochloride solution.
[0013] In step (3), the pre-filled syringe or injection needle must comply with relevant national standards to ensure the functionality, sealing and safety of the drug delivery system.
[0014] The tests in step (3) include appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue, and bacterial endotoxin content. Specifically: The product appears as a white, milky white, or slightly yellow viscous suspension, free of visible foreign matter, reflecting the inherent characteristics of the product (collagen color), and ensuring the absence of foreign particles to guarantee injection safety. The pH value is 7.0-7.5; The osmolar concentration is 280-360 mOsmol / kg to ensure that it is isotonic or nearly isotonic with human body fluids, thus avoiding cell dehydration or edema after injection. The heavy metal content is ≤10μg / g, and the production process strictly controls the introduction of harmful heavy metal impurities, in accordance with the strict requirements of the Chinese Pharmacopoeia for implantable medical devices. The residual amount of glutaraldehyde is ≤2μg / mL. Glutaraldehyde has certain cytotoxicity and its residue must be strictly controlled. This limit is based on toxicological assessment to ensure the safety of clinical use. The bacterial endotoxin is ≤0.5 EU / mL. As a Class III medical device implanted in the human body, bacterial endotoxin must be strictly controlled for pyrogens introduced from raw materials or the production process to avoid adverse reactions such as fever after injection.
[0015] The application of the lidocaine-containing cross-linked collagen implant is as follows: the lidocaine-containing cross-linked collagen implant is injected into the dermis to correct moderate to severe nasolabial folds.
[0016] This invention relates to a lidocaine-containing cross-linked collagen implant. Through chemical cross-linking modification of natural collagen, combined with freeze-drying and aseptic manufacturing processes, a safe, durable collagen implant containing anesthetic components is prepared. The preparation process first involves dispersing type I collagen in PBS buffer to obtain a collagen solution, then adding glutaraldehyde aqueous solution to obtain a cross-linked collagen wet material. The concentration, amount, and rate of addition of glutaraldehyde directly determine the degree of cross-linking, thus affecting the product's durability, mechanical properties, and immunogenicity. Too low a cross-linking level results in rapid degradation, while too high a level leads to an overly hard product, affecting injection smoothness and tissue compatibility. Subsequently, the cross-linked collagen wet material is vacuum freeze-dried to form a porous, sponge-like freeze-dried cake, which is then irradiated for sterilization. This step requires careful control of the pre-freezing rate during the vacuum freezing stage and the vacuum level and temperature control during the irradiation sterilization stage. Inappropriate freeze-drying profiles can lead to collagen structure collapse, difficulty in reconstitution, or unacceptable moisture content, affecting the final product's viscosity and injectability. Finally, the sterile cross-linked collagen freeze-dried cake is redispersed in sterile PBS buffer containing sodium chloride and phosphate, homogenized, and then mixed thoroughly with sterile lidocaine hydrochloride solution. The mixture is then filled and sealed to obtain the lidocaine-containing cross-linked collagen implant. This step is the most critical control point, and a sterile environment must be maintained throughout the process, including the transfer of sterile intermediates, the maintenance of a sterile environment, the use of sterile instruments, and the standard operating procedures for personnel, to ensure that the final product passes the sterility test.
[0017] Collagen is widely available, structurally similar to human collagen, and its immunogenicity can be effectively controlled through mature processes. Type I collagen is the most abundant type of collagen in the skin and determines the skin's tensile strength. This invention selects type I collagen as the core functional material to provide immediate filling support, correct wrinkles and depressions, and serve as an extracellular matrix template to guide host cell ingrowth and stimulate autologous collagen regeneration.
[0018] This invention selects glutaraldehyde, which has high cross-linking efficiency, as a cross-linking agent to covalently cross-link with free amino groups on collagen molecules, forming a stable bridging structure. The addition of the cross-linking agent can significantly improve the mechanical strength of collagen and resist rapid degradation by collagenases in vivo, thereby prolonging the duration of the filling effect; at the same time, cross-linking modification can mask antigen sites and effectively reduce the immunogenicity of the product.
[0019] Lidocaine hydrochloride, as a local anesthetic, acts on local nerve endings, reversibly blocking the generation and conduction of nerve impulses, thereby reducing pain during injection. Lidocaine hydrochloride is a recognized safe local anesthetic in domestic and international drug guidelines, with rapid onset and a duration suitable for injection procedures; premixed in the product, it can be used immediately, avoiding additional pre-operative preparation and waiting, thus optimizing the treatment process.
[0020] Disodium hydrogen phosphate and potassium dihydrogen phosphate together form the PBS buffer system to maintain the product within the physiological pH range throughout storage and use. This is crucial for maintaining the stability of the natural triple helix structure of collagen, ensuring the efficacy of lidocaine, and guaranteeing good tissue compatibility after injection, thereby minimizing post-injection irritation.
[0021] Sodium chloride and potassium chloride are used as osmotic pressure regulators to adjust the osmotic pressure of the product, making it isotonic with human body fluids. Injecting isotonic solutions can avoid osmotic pressure damage or irritation to tissue cells, reduce postoperative edema and pain, and improve safety.
[0022] This invention also incorporates functional monosaccharides, which are one or more of α-galactose, glucose, and β-mannose. These monosaccharides, through their hydroxyl groups, can form stable hydrogen bonds with the amino and carboxyl groups of collagen, synergistically activating fibroblasts to synthesize autologous collagen. This significantly enhances the skin's water-binding and water-locking capacity after surgery, improving skin hydration. Simultaneously, it can fill tiny gaps in the collagen cross-linking network, reduce porosity expansion of the collagen scaffold under high temperatures, lower the risk of lidocaine molecule degradation or migration, prolong the retention time of active ingredients, and improve the thermal stability of the cross-linked collagen implant.
[0023] The beneficial effects of this invention are: Compared with existing technologies, the lidocaine-containing cross-linked collagen implant of this invention is not simply a physical filler, but rather a multi-faceted and multi-directional synergistic effect encompassing physical filling and support, cell scaffold guidance and tissue integration, and degradation and replacement. Specifically: The role of physical filling and support: After injection, the viscoelastic collagen gel immediately fills the tissue defects in the dermis, providing immediate support for wrinkles and depressions, and smoothing wrinkles instantly.
[0024] The role of cell scaffold guidance and tissue integration: The injected cross-linked collagen forms a three-dimensional extracellular matrix scaffold in vivo. The host's own fibroblasts and capillary endothelial cells recognize this well-compatible scaffold and migrate and attach along it, thus playing a role in cell scaffold guidance. This scaffold provides cells with the correct growth direction and spatial structure, guiding fibroblasts to synthesize and secrete new autologous collagen and elastic fibers in an orderly manner, thereby initiating the real tissue regeneration process.
[0025] The role of degradation and replacement: Exogenous cross-linked collagen is slowly degraded by the body's collagenase. At the same time, under its guidance, the autologous collagen network is constantly maturing and strengthening, achieving a balance between metabolism and regeneration. As exogenous collagen is degraded, newly generated autologous collagen tissue will gradually replace its space, maintaining the filling effect. Therefore, even after exogenous collagen is completely metabolized, the autologous tissue awakened and guided by it still exists, thus achieving a natural, lasting, and long-lasting rejuvenation effect. Detailed Implementation
[0026] The parameters of the specific chemical substances used in the examples are from the following sources: The water used in the examples was water for injection.
[0027] Type I collagen: Manufacturer: Beijing Bairuiji Biotechnology Co., Ltd., Product No.: BN39879.
[0028] The preparation method of sterile PBS buffer is as follows: Add 8g of sodium chloride and 0.2g of potassium chloride to 800mL of deionized water and stir for 0.5 hours. Then add 1.44g of disodium hydrogen phosphate and 0.24g of potassium dihydrogen phosphate and continue stirring for 0.5 hours. Adjust the pH to 7.4 with 1M NaOH solution and 0.1M HCl solution, and bring the volume to 1000mL. Autoclave at 121℃ for 20min. After sterilization, dispense into sterile bottles and store at 4℃.
[0029] Example 1 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution. 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen. 1000g of water was added to the cross-linked collagen and centrifuged to wash it. Then 1000g of 3.6wt% lysine aqueous solution was added, and finally 1000g of water was added to the cross-linked collagen and centrifuged to wash it to obtain cross-linked collagen wet material. (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is freeze-dried in vacuum at 0.33 mbar and -60℃ to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 15 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production conditions, 2.5g of sterile cross-linked collagen freeze-dried cake was redispersed in 350g of sterile PBS buffer and homogenized to make it a uniform viscous suspension; 15g of 8wt% sterile lidocaine hydrochloride solution was added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately, sent for testing. The appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue, and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0030] Example 2 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution. 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen. 1000g of water was added to the cross-linked collagen and centrifuged to wash it. Then 1000g of 3.6wt% lysine aqueous solution was added, and finally 1000g of water was added to the cross-linked collagen and centrifuged to wash it to obtain cross-linked collagen wet material. (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is freeze-dried in vacuum at 0.33 mbar and -50℃ to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 15 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production conditions, 2.5g of sterile cross-linked collagen freeze-dried cake was redispersed in 350g of sterile PBS buffer and homogenized to make it a uniform viscous suspension; 0.8g of α-galactose and 15g of 8wt% sterile lidocaine hydrochloride solution were added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately. After testing, the appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0031] Example 3 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution. 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen. 1000g of water was added to the cross-linked collagen and centrifuged to wash it. Then 1000g of 3.6wt% lysine aqueous solution was added, and finally 1000g of water was added to the cross-linked collagen and centrifuged to wash it to obtain cross-linked collagen wet material. (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is freeze-dried in vacuum at 0.33 mbar and -60℃ to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 15 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production conditions, 2.5g of sterile cross-linked collagen freeze-dried cake was redispersed in 350g of sterile PBS buffer and homogenized to make it a uniform viscous suspension; 0.8g of glucose and 15g of 8wt% sterile lidocaine hydrochloride solution were added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately. After testing, the appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0032] Example 4 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution. 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen. 1000g of water was added to the cross-linked collagen and centrifuged to wash it. Then 1000g of 3.6wt% lysine aqueous solution was added, and finally 1000g of water was added to the cross-linked collagen and centrifuged to wash it to obtain cross-linked collagen wet material. (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is freeze-dried in vacuum at 0.33 mbar and -60℃ to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 15 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production conditions, 2.5g of sterile cross-linked collagen freeze-dried cake was redispersed in 350g of sterile PBS buffer and homogenized to make it a uniform viscous suspension; 0.8g of β-mannose and 15g of 8wt% sterile lidocaine hydrochloride solution were added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately. After testing, the appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0033] Example 5 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution. 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen. 1000g of water was added to the cross-linked collagen and centrifuged to wash it. Then 1000g of 3.6wt% lysine aqueous solution was added, and finally 1000g of water was added to the cross-linked collagen and centrifuged to wash it to obtain cross-linked collagen wet material. (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is freeze-dried in vacuum at 0.33 mbar and -60℃ to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 15 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production conditions, 2.5g of sterile cross-linked collagen freeze-dried cake was redispersed in 350g of sterile PBS buffer and homogenized to make it a uniform viscous suspension; 0.4g of glucose, 0.4g of β-mannose and 15g of 8wt% sterile lidocaine hydrochloride solution were added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately. After testing, the appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0034] Comparative Example 1 A method for preparing a lidocaine-containing cross-linked collagen implant, the specific steps of which are as follows: (1) Collagen dissolution and cross-linking: 3.5g of type I collagen was dispersed in 350g of sterile PBS buffer and stirred at 500rpm for 1 hour to form a homogeneous collagen solution; 15g of 4wt% glutaraldehyde aqueous solution was added dropwise and stirred at 5℃ for 24 hours to obtain cross-linked collagen; 1000g of water was added to wash the cross-linked collagen by centrifugation to obtain cross-linked collagen wet material; (2) Wet irradiation sterilization: The cross-linked collagen wet material obtained in step (1) is packaged in a clean environment into sterile polyethylene bags or sterile glass bottles, sealed, and then irradiated at 2-8℃ with an irradiation dose of 15kGy to obtain sterile cross-linked collagen wet material. (3) Final product preparation and filling: Under aseptic production conditions, the solid content of the cross-linked collagen wet material was pre-determined using the conventional drying method (drying at 105℃ to constant weight). Based on the determination results, the mass of wet material required to produce 2.5g of cross-linked collagen dry base was calculated. The cross-linked collagen wet material was weighed according to the calculated mass and added to 350g of sterile PBS buffer. It was homogenized to make it into a uniform viscous suspension. Then, 15g of 8wt% sterile lidocaine hydrochloride solution was added and stirred for 10min until the solution appeared uniform without obvious layering or particles. The solution was sent for testing. Finally, it was filled into pre-filled syringes or injection needles and sealed immediately. The appearance, pH value, osmolar concentration, heavy metal impurity content, glutaraldehyde residue, and bacterial endotoxin content all met the standards, and the lidocaine-containing cross-linked collagen implant was obtained.
[0035] Compared with Example 1, this comparative example did not add lysine aqueous solution to block residual glutaraldehyde during the cross-linked collagen washing process, and omitted the vacuum freeze-drying step. The final product was directly prepared after irradiation sterilization in a wet state. This was used to compare and illustrate the effects of lysine blocking and freeze-drying processes on reducing cytotoxicity and improving product stability.
[0036] Test Example 1 The formation of nasolabial folds is mainly related to collagen loss, decreased skin elasticity, facial expression habits, and weakened facial bone support. Eighteen female volunteers, aged 35-40 years (mean age 37.5 years), were selected and divided into a control group and experimental groups (Examples 1-5). The control group received type I collagen injections, while the experimental groups received lidocaine-containing cross-linked collagen implants (Examples 1-5). The injection site was the nasolabial folds, the injection layer was the dermis, and the injection point was the tear trough depression. The injection volume per side was 0.5 mL, with a total volume of 1 mL. After the injection and shaping, facial massage was avoided, and sun protection was recommended.
[0037] Before and 90 days after the operation, the skin moisture content of volunteers in the control group and the experimental groups of Examples 1-5 was scored using a multifunctional skin test instrument (MPA10, CK GmbH, Germany). The average value of the data was taken and summarized as shown in Table 1. The total score for each item was 100 points.
[0038] Table 1
[0039] The core reason for the difference in skin moisture content data in Test Example 1 lies in the functional differences of the components of the implants in each group. The type I collagen used in the control group can only serve as a basic scaffold to provide attachment sites for fibroblasts and guide cell proliferation and differentiation to promote autologous collagen regeneration. However, it has not undergone cross-linking treatment, resulting in a loose structure between collagen molecules and insufficient stability. It can only achieve basic water binding by relying on its own small number of hydroxyl groups and cannot form a long-lasting and stable hydration environment. The collagen implant in Example 1 uses type I collagen as its core and introduces lidocaine as a local anesthetic. However, because no functional monosaccharides are added, its moisturizing ability relies solely on the properties of collagen itself. The collagen implants in Examples 2-4, based on Example 1, add α-galactose, glucose, and β-mannose, respectively. The hydroxyl groups of the monosaccharide molecules can form stable hydrogen bonds with the amino and carboxyl groups of collagen, constructing a more durable hydration layer. At the same time, they work synergistically with the collagen scaffold to further activate fibroblasts to synthesize autologous collagen and enhance the skin's own water-locking ability. Among them, Example 4 shows better results. Example 5 uses glucose and β-mannose in combination. The two monosaccharides work synergistically to improve skin hydration. Glucose binds tightly to collagen with its highly active hydroxyl groups, while β-mannose forms a dense and stable hydrogen bond network, which improves skin water retention and postoperative skin moisture content.
[0040] Test Example 2 Take 1g of each of the lidocaine-containing cross-linked collagen implants prepared in Examples 1-5 and place them in centrifuge tubes, seal them, and incubate them at 40°C for 3 hours. Measure the initial lidocaine content and the content at the 3rd hour in the lidocaine-containing cross-linked collagen implants prepared in Examples 1-5. Prepare 3 sets of samples for each example, and take the average value of the data, which is summarized in Table 2.
[0041] Table 2
[0042] In Example 1, the lidocaine-containing cross-linked collagen implant did not contain any functional monosaccharides. At high temperatures, the increased thermal motion of collagen molecules led to a slight expansion of the scaffold pores. Lidocaine molecules were prone to slight degradation or migration, and their content decreased after being placed in a 40°C environment for 3 hours. Examples 2-4 added α-galactose, glucose, and β-mannose, respectively, to Example 1. The hydroxyl groups in the α-galactose molecules added in Example 2 can form basic hydrogen bonds with the amino and carboxyl groups of the collagen side chains, filling the tiny gaps in the collagen scaffold. In Example 3, glucose, as an endogenous monosaccharide, has better biocompatibility with collagen, and its hydroxyl activity is higher than that of α-galactose, which can more tightly reinforce the collagen cross-linked network, reduce the expansion of scaffold pores at high temperatures, and enhance stability. In Example 4, the addition of β-mannose hydroxyl groups can form a denser and more stable hydrogen bond network, improving the collagen's heat resistance. Example 5 uses a combination of glucose and β-mannose to further enhance the stability of lidocaine through the synergistic effect of the two monosaccharides. Glucose, with its endogenous advantage, forms a tight bond with collagen, which significantly inhibits the expansion of scaffold pores at high temperatures. β-mannose can enhance the thermal stability of the material through the dual effects of hydrogen bonding and hydrophobic interaction.
[0043] Test Example 3 In vitro cytotoxicity evaluation of lidocaine-containing cross-linked collagen implants Experimental objective: To evaluate the in vitro cytotoxicity (cell viability) of lidocaine-containing cross-linked collagen implants obtained in Examples 1-5 and Comparative Example 1 on L929 fibroblasts using the MTT assay, and to compare the effects of different formulations and processes on cell compatibility.
[0044] This test was conducted in accordance with the following standards: GB / T 16886.5-2017 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity tests"; GB / T 16886.12-2023 Biological evaluation of medical devices - Part 12: Sample preparation and reference materials.
[0045] Basic principle: L929 mouse fibroblasts were used as the experimental cell line. Extracts were prepared from the products obtained in Examples 1-5 and Comparative Example 1 according to the standard extraction conditions. L929 cells were incubated with extracts of different concentrations, and cell metabolic activity was measured using the MTT assay to calculate cell viability. When the cell viability in the 100% extract treatment group was ≥70%, the sample was considered to have no potential cytotoxicity.
[0046] Test sample The lidocaine-containing cross-linked collagen implants prepared in Examples 1-5; The finished product of the cross-linked collagen implant containing lidocaine prepared in Comparative Example 1.
[0047] Cells and Culture Media Cell line: L929 mouse fibroblasts, purchased from Wuhan Pronosei Life Science Technology Co., Ltd., the cells passed the cell identification and were free of mycoplasma contamination; Basic culture medium: MEM medium containing L-glutamine; Supplemental ingredients: 10% (volume fraction) fetal bovine serum (FBS), 1 wt% penicillin and streptomycin mixed antibiotics; The experimental extraction medium was MEM medium containing 10 vt% FBS.
[0048] Reference materials Negative control: High-density polyethylene resin (HDPE), sterilized by autoclaving (121℃, 20min). Positive control: Disposable medical rubber examination gloves (latex gloves), cut to the specified area according to standard requirements before use.
[0049] Blank control: MEM culture medium containing only 10% FBS (without contact with the sample).
[0050] Main instruments and equipment CO2 incubator: 37℃, 5% CO2, saturated humidity; Biosafety cabinets or clean benches: used for aseptic operations; Inverted microscope: used for observing cell morphology; 96-well cell culture plate; Full-wavelength microplate reader: equipped with a 570nm detection wavelength and a 650nm reference wavelength; Tabletop constant temperature shaking incubator; Low-speed centrifuges, electronic balances, and other conventional experimental equipment.
[0051] Main reagents D-Hanks buffer; 0.25% trypsin solution; MEM medium and MEM medium without phenol red; Fetal bovine serum (FBS); Double antibiotic (penicillin-streptomycin solution); MTT reagent (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) was prepared as a 1 mg / mL working solution; Isopropanol (used to dissolve MTT reduction products).
[0052] Preparation of sample extract Extracts were prepared from the finished samples of Examples 1-5 and Comparative Example 1 according to the requirements of GB / T 16886.12-2023, under the following conditions: (1) Sampling and proportion: For each sample, weigh a certain mass m of the finished product and add it to MEM medium containing 10% FBS that has been pre-equilibrated to 37℃ at a mass-volume ratio of 0.2 g / mL. For example, when preparing 10 mL of extract, weigh 2.0 g of sample and add it to 10 mL of medium; (2) Extraction conditions: After sealing the sterile container containing the sample and culture medium, place it in a constant temperature shaking incubator at 37℃ and rotate at 60 rpm for 72 h.
[0053] (3) Post-processing: After extraction, observe the appearance of the extract. If there are no abnormal lumps or obvious precipitation, filter with a 0.22μm sterile filter membrane to remove particles and microorganisms. Collect the filtrate as 100% sample extract, store it at 2-8℃ for a short period of time and use it within 24 hours.
[0054] (4) Preparation of control extract: negative control: HDPE was extracted at the same mass-volume ratio of 0.2 g / mL in MEM medium containing 10% FBS for 72 h at 37 °C and 60 rpm. The negative control extract was obtained after filtration through a 0.22 μm filter membrane. Positive control: Press the latex gloves 6cm apart. 2 The surface area-volume ratio was / mL in MEM medium containing 10% FBS, and the extract was extracted at 37℃ and 60rpm for 72h. After filtration through a 0.22μm filter membrane, the positive control extract was obtained. Blank control: MEM medium containing 10% FBS was used directly without contact with any materials.
[0055] (5) Extract gradient: Using 100% extract as the mother liquor, four concentration gradients of 75%, 50%, and 25% were prepared by dilution with culture medium: 75%: Take 750 μL of 100% extract + 250 μL of culture medium; 50%: Take 500 μL of 100% extract + 500 μL of culture medium; 25%: Take 250 μL of 100% extract + 750 μL of culture medium.
[0056] MTT cytotoxicity assay Cell inoculation (1) Wash L929 cells in good growth condition once with D-Hanks buffer, add an appropriate amount of 0.25% trypsin solution to digest, and gently pipette to make the cells into a single cell suspension. (2) Terminate digestion with MEM medium containing 10% FBS, centrifuge to remove supernatant, resuspend and count, and adjust cell concentration to 1×10⁻⁶. 5 cells / mL; (3) Seed the cell suspension at 100 μL / well in a 96-well plate, approximately 1 × 10⁶ cells per well. 4 One cell; (4) Place the cells in a 37℃, 5% CO2 incubator for 24h to allow them to adhere to the wall and enter the logarithmic growth phase.
[0057] Sample addition and incubation After 24 hours, discard the culture medium from each well and use the following grouping method, with 6 replicates per group: Blank control group: Add 100 μL of blank culture medium; Negative control group: Add 100 μL of negative control extract (100%). Positive control group: Add 100 μL of positive control extract (100%). For each sample group: add 100 μL of the corresponding 100% extract of Examples 1-5 and Comparative Example 1; if necessary, different concentration gradients such as 75%, 50%, and 25% can be set simultaneously.
[0058] After adding the extraction solution, the 96-well plate was placed in a 37°C, 5% CO2 incubator and incubated for another 24 hours.
[0059] MTT colorimetric assay and OD determination (1) After incubation for 24 hours, discard the extract from each well and add 50 μL of 1 mg / mL MTT working solution to each well; (2) Continue incubation at 37℃ and 5% CO2 for 2 hours to allow the mitochondria in living cells to reduce MTT to insoluble purple formazan crystals; (3) After incubation, discard the supernatant of each well, add 100 μL of isopropanol to each well, and place it on a shaker at 37°C and about 60 rpm to dissolve the formazan crystals for 30 min. (4) The absorbance (OD) of each well was measured using an ELISA reader at a wavelength of 570 nm. 570 Background subtraction was performed using 650nm as the reference wavelength.
[0060] 5.4 Result Calculation and Judgment (1) Cell viability is calculated using the following formula: Cell viability (%) = 100 × OD 570 (Sample group) / OD 570 (Blank control group) OD 570 (Sample group) refers to the average OD value of a sample group treated with 100% extract.570 (Blank control group) is the average OD value of the blank control group.
[0061] (2) Judgment criteria: Quantitative evaluation: If the cell viability rate of the 100% extract treatment group is <70%, the sample is considered to have potential cytotoxicity; if it is ≥70%, the sample is considered to have no potential cytotoxicity. Qualitative evaluation: Cell morphology was observed under an inverted microscope, and cytotoxicity was graded from 0 to 4 according to Appendix A of GB / T16886.5-2017. A grade >2 was considered to be cytotoxic.
[0062] Test results Under the above experimental conditions, the cell viability results of the 100% extract treatment groups of Comparative Example 1 and Examples 1-5 are summarized in Table 3 (n=6, results are averaged): Table 3. Cell viability test results (MTT method, 100% extract).
[0063] Meanwhile, under a microscope, the morphology of each group of cells was observed. No obvious shrinkage, shedding or dissolution was observed in the cells of Comparative Example 1 and Samples 1-5. A small number of discrete particles were visible in the cytoplasm. There was no obvious inhibition of proliferation. The cytotoxicity morphological qualitative grade was 0.
[0064] As can be seen from Table 3: (1) The cell survival rate of Comparative Example 1 was 75%, which was higher than the standard limit of 70% and was judged to have no obvious potential cytotoxicity. However, it was lower than that of Examples 1-5, suggesting that it had a strong adverse effect on cells. (2) The cell survival rates of Examples 1-5 were all in the range of 91.83%-95.5%, which were significantly higher than those of Comparative Example 1. This indicates that by introducing lysine to block residual glutaraldehyde during the cross-linking washing stage and combining it with the freeze-drying-resolution process, the residual small molecules and active carbonyl groups in the cross-linked collagen can be effectively reduced, thereby reducing cytotoxicity and improving cell survival rate. (3) Based on Example 1, Examples 2-5 further added α-galactose, glucose, β-mannose and their combinations. The cell survival rate showed a gradual upward trend, indicating that in addition to improving the water retention and thermal stability of the material, functional monosaccharides can also have a synergistic optimization effect on cell compatibility by improving the collagen network microenvironment and reducing the migration of irritating small molecules.
[0065] Based on the combined results of quantitative cell viability and qualitative cell morphology observations, the lidocaine-containing cross-linked collagen implants prepared in Examples 1-5 showed no potential cytotoxicity, and their cell compatibility was significantly better than that of the Comparative Example 1 sample, which did not contain lysine and was not lyophilized. The above experimental methods and results meet the requirements of GB / T16886.5-2017 and GB / T16886.12-2023, and can serve as important evidence demonstrating the good cell compatibility of the products of this invention.
[0066] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method for preparing a lidocaine-containing cross-linked collagen implant, characterized in that, The specific steps are as follows, by weight: (1) Collagen dissolution and cross-linking: Disperse 3-4 parts of type I collagen in 80-90 parts of PBS buffer, stir at 400-600 rpm for 0.5-1.5 hours to form a homogeneous collagen solution, add 10-20 parts of glutaraldehyde aqueous solution and stir at 2-8℃ for 22-26 hours to obtain cross-linked collagen, add 900-1100 parts of water to centrifuge and wash the cross-linked collagen, add 900-1100 parts of 3-4wt% lysine aqueous solution, and finally add 900-1100 parts of water to centrifuge and wash the cross-linked collagen to obtain cross-linked collagen wet material; (2) Primary freeze-drying and irradiation sterilization: The cross-linked collagen wet material is vacuum freeze-dried to form a porous sponge-like freeze-dried cake, and then irradiated for sterilization. The irradiation sterilization dose is 10-20 kGy to obtain a sterile cross-linked collagen freeze-dried cake. (3) Final product preparation and filling: Under aseptic production process environment, 1-3 parts of sterile cross-linked collagen freeze-dried cake are redispersed in 360-380 parts of sterile PBS buffer and homogenized to make it into a uniform viscous suspension; 0.6-1 parts of functional monosaccharide and 10-20 parts of sterile lidocaine hydrochloride solution are added and mixed evenly, sent for testing, and finally filled into pre-filled syringes or injection needles and sealed immediately to obtain the lidocaine-containing cross-linked collagen implant; The functional monosaccharides in step (3) are glucose and β-mannose; In step (3), the sterile lidocaine hydrochloride solution is a 5-10 wt% sterile lidocaine hydrochloride solution.
2. The method for preparing the lidocaine-containing cross-linked collagen implant as described in claim 1, characterized in that, The concentration of the glutaraldehyde aqueous solution in step (1) is 3-5 wt%.
3. A lidocaine-containing cross-linked collagen implant, characterized in that, It is prepared by the preparation method described in claim 1 or 2.
4. The use of the lidocaine-containing cross-linked collagen implant as described in claim 3 in the preparation of a formulation for correcting moderate to severe nasolabial folds.
Citation Information
Patent Citations
Human skin beautifying and wrinkle-removing filling agent and preparation method thereof
CN113797389A
Injection type facial filling agent composition for cosmetic and plastic surgery and preparation method of injection type facial filling agent composition
CN117085178A
Association of monosaccharides and C-glycoside derivatives and its use in cosmetics
CN101766546A
Collagen implant and preparation method thereof
CN107213028A
Method for preparing toughened and high-cell-compatibility biological protein fiber based on secondary cross-linking system
CN117904739A